A CASE STUDY OF OCCUPANT ENVIRONMENTAL COMFORT AT AUTOMOTIVE ASSEMBLYWORKSTATION - A. R. , Ismail; N. , Jusoh; A. P. , Puvanasvaran; M. S. , Reza (2010)
The environmental factors assessment in the building has become a popular research area over the past decade. However, how the service life of a building affects the results of the environmental assessment of a building has not been emphasized previously. The aim of this study is to analyze how structural solutions and building design affect the results of the environmental assessment. Furthermore, how the environmental factors affects the productivity is analyzed. The environmental assessments in building were calculated for this study by Environment Factors Equipment. The current situation and the future of the environmental assessment of buildings are discussed. In addition, topics for further research are suggested which is the environmental impact of an occupant should be studied. The research concludes that comfort and productivity in the workplace is related more to design factors.